2021
DOI: 10.1155/2021/6642973
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Molecular Imaging of the Efficacy of Aminopeptidase N (APN/CD13) Receptor Inhibitor Treatment on Experimental Tumors Using 68Ga‐NODAGA‐c(NGR) Peptide

Abstract: Introduction. The aminopeptidase N (APN/CD13) receptor plays an important role in the neoangiogenic process and metastatic tumor cell invasion. Clinical and preclinical studies reported that bestatin and actinonin are cytotoxic to APN/CD13-positive tumors and metastases due to their APN/CD13-specific inhibitor properties. Our previous studies have already shown that 68Ga-labeled NGR peptides bind specifically to APN/CD13 expressing tumor cells. The APN/CD13 specificity of 68Ga-NGR radiopharmaceuticals enables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Five days after injecting bestatin and actinonin, the PET scans showed that bestatin- and actinonin-treated B16-F10 tumours exhibited significantly low radiopharmaceutical uptake and accumulation. This means that the CD13 inhibitor may be suitable for suppressing the neoangiogenic process [ 154 ]. A comparative study of monomeric 68 Ga-NODAGA-NGR and dimeric 68 Ga-NODAGA-NH 2 was published by Ina Israel and colleagues in 2021.…”
Section: Radiolabelled Peptides Used In Cancer Theragnosismentioning
confidence: 99%
“…Five days after injecting bestatin and actinonin, the PET scans showed that bestatin- and actinonin-treated B16-F10 tumours exhibited significantly low radiopharmaceutical uptake and accumulation. This means that the CD13 inhibitor may be suitable for suppressing the neoangiogenic process [ 154 ]. A comparative study of monomeric 68 Ga-NODAGA-NGR and dimeric 68 Ga-NODAGA-NH 2 was published by Ina Israel and colleagues in 2021.…”
Section: Radiolabelled Peptides Used In Cancer Theragnosismentioning
confidence: 99%
“…Previous studies already reported that B16-F10 melanoma tumors showed strong positivity for APN/CD13 and galectin-3 receptors [23,32,33]. For the determination of receptor targeting potential and biodistribution of the [ 68 Ga]-11, [ 68 Ga]-3, [ 68 Ga]-9, and [ 68 Ga]-10 radiotracers in vivo PET imaging studies and ex vivo tissue distribution studies were performed using B16-F10 melanoma tumor-bearing mice.…”
Section: Diccussionmentioning
confidence: 99%
“…Studies have reported that APN/CD13 is overexpressed in endothelial cells of the tumor vascular network and in some solid tumors (melanoma, prostate carcinoma, lung cancer, pancreatic adenocarcinoma, ovarian cancer, breast cancer, colon cancer, etc.). Because of the increased expression, APN/CD13 can be regarded not only as an important clinical marker in some inflammatory diseases and malignancies, but also as a suitable target for antitumor and anti-inflammatory therapy [ 15 ]. The accessible location of the target (i.e., the tumor vascular network) and the high specificity of the ligand make NGR a suitable candidate for active targeting of macromolecule or nanoparticle systems in vivo.…”
Section: Introductionmentioning
confidence: 99%